Coordinated flying with unmanned aircraft - Chua, Damian Gaocong (Nanyang Technological University, 2022)
The phrase "strength in numbers" is a frequent idiomatic statement that can be used to a variety of real-life situations. The streamlined movement of an army of ants, the seemingly random shoaling of fish, the swarming of bees, the flying formation of migrating geese, the herding behavior of graceful movement of elephants, and so on, are some illustrative examples of what one might call real-life "strength in numbers" in action. In the commercial scenario, most swarm drones use their inbuilt GPS module to position the drone wherever the programmer wants it to be. A networked control system will be employed if the GPS module is not used. Although the above two approaches are the most utilized, in this project, we want to construct very low-cost micro-drones that will not have the GPS module nor the capability to communicate with another drone. This project focuses on flight stability to allow the drone to move from one location to another without problems, and we'd like to use simple programming to group the drones together and fly in formation.